A clinical and immunological study on late onset Myasthenia Gravis - Sadalage, Girija (2021)
Myasthenia gravis is an autoimmune disorder of neuromuscular transmission caused by antibodies to the acetylcholine receptor and related components on the post synaptic membrane of the neuromuscular junction. Recent evidence has shown that the incidence of late-onset myasthenia gravis, defined as onset at more than 50 years of age, has been increasing. We sought to prospectively recruit patients newly diagnosed with myasthenia gravis and look at their clinical and immunological profile to see if there are any differences between early onset and late-onset myasthenia gravis.